Male median raphe cysts: serial retrospective analysis and histopathological classification - Shao I-Hung; Chen Tai-Di; Shao Hsiang-Te; Chen Hsiao-Wen (BMC, 2012)
Abstract Background To review the clinical and pathological characteristics of median raphe cysts and to classify the lesions according to pathogenesis and histopathological findings. Methods The medical records of patients who were diagnosed with median raphe cysts between 2001 and 2010 were reviewed to document the clinical presentation and pathological findings of the cysts. Results Most patients were asymptomatic; however, 9 patients had inflammatory or infectious cysts that were tender or painful. Four patients who had cysts on the parameatus and distal prepuce had difficulty voiding. Hematuria and hematospermia were noted in 2 cases. Thirty-one cysts were lined with an urothelium-like epithelium, and a squamous epithelium lining was found in 3 cases. In 2 cases, a well-formed mucinous glandular structure was observed. The other 20 cysts consisted of mixed epithelia. After excision of the cysts under local or general anesthesia, an urethral fistula developed as a complication in only 1 case. Conclusions Median raphe cysts are benign lesions formed due to tissue trapping during the development of urethral folds. The cysts can be defined into 4 types based on pathological findings: urethral, epidermoid, glandular, and mixed. The associated symptoms and signs should be taken into consideration when determining the treatment for the cysts. Virtual slides The virtual slide(s) for this article can be found here: http//http://www.diagnosticpathology.diagnomx.eu/vs/7727074877500751